In vitro effects of melatonin on hyaluronidase activity and sperm motility in bull semen - Tanyildizi, Sadettin; Bozkurt, Tanzer; Ciftci, Osman; Sakin, Fatih (Tubitak Scientific & Technological Research Council Turkey, 2006)
The effects of melatonin on hyaluronidase activity of semen and spermatozoa motility of Holstein bulls were investigation in vitro. Semen samples were divided into 5 equal parts and incubated (v/v) with melatonin at the doses of 0.5, 1, 2 and 4 mM for 60 min. Percentages of spermatozoa motility, morphological abnormality and hyaluronidase activity of semen were determined at 5, 10, 15, 20, 30 and 60 min during incubation. Results show that melatonin caused a significant (P < 0.001) decrease in the spermatozoa motility, while causing a significant increase in the hyaluronidase activities of the semen. However, there was no significant difference in the percentages of abnormal spermatozoa when compared with control samples. Doses of 0.5, 1, 2 and 4 mM of melatonin in bull semen decreased the percentage of spermatozoa motility in a time- and dose-dependent manner. The mean percentages of abnormal spermatozoa were not affected by melatonin treatment. However, it caused an increased hyaluronidase activity of bull semen. In conclusion, the existence of melatonin in bull semen has a significant effect on fertilization ability by affecting spermatozoa motility and hyaluronidase activity.
Keywords: bull spermatozoa; semen; melatonin; hyaluronidase